THE LEVEL OF SUITABILITY OF PHYSICS MATERIAL IN THE PHYSICS EDUPARK E-BOOK OF SARASAH KAJAI WATERFALL IN REVIEW OF THE 2013 CURRICULUM AND THE INDEPENDENT CURRICULUM - Vrimesty, Etri Alga (PILLAR OF PHYSICS EDUCATION, 2024)
E-books are textbooks in electronic form containing text, figures and videos created and distributed via computers or cell phones. Yunita (2022) has developed an inserted high school physics edupark E-book of Sarasah Kajai Waterfall Destination and a approach by scientific to the revolution of industrial at 4.0 by utilizing the waterfall as an edupark or educational park. The developed e-book still uses the curriculum of 2013. The curriculum of 2013  prioritizes learning with a scientific approach while the independent curriculum optimizes content with means students have many opportunities to learn concepts and strengthen competency skills. The research purpose was to reveal the suitability level of the material in the physics edupark E-book of Sarasah Kajai Waterfall in terms of the 2013 curriculum and the independent curriculum. The type of research used is research of descriptive and approach by qualitative. The population in this research includes all Physics Edupark E-books and Independent Curriculum SMA/MA Physics Books used by SMA/MA in West Sumatra. The research samples were the Physics Edupark E-book Sarasah Kajai Waterfall and the Physics Book for SMA/MA class X and XI in 2022 Independent Curriculum published by Erlangga with the author Ni Ketut Lasmi. Material suitability data uses research analysis instruments and techniques for data collection are conducted by documentation studiesThe level of suitability of material physics is measured based on three dimensions of knowledge (factual, conceptual and procedural). The finding shown that the level of suitability of the material in the Sarasah Kajai waterfall physics edupark e-book was 80% categorized as appropriate. Thus, the conclusion that the Sarasah Kajai Waterfall Physics Edupark E-book is in accordance with the Independent Curriculum SMA/MA Physics Book.